In process of time - Citradewi, Carla Gabriela (2018)
The research sought to investigate personal and interpersonal detachment and discomfort regarding unresolved past events and family relationship. Divided into two parts, self-awareness and shift of perspective, the investigation revolves around the personal history of the author and her parents. The process of examination involves self-reflection through writing and art-making, conversations with the author’s mother and significant others, and literature reviews on relevant subject matters. The journey was then translated into an image-based installation, including two-channel projection of performance video with sound and a photobook in an enclosed space.